Measurement of physicochemical and heavy metals concentration in drinking water from sources to consumption sites in Peshawar, Pakistan - Yousaf, Saeeda; Ilyas, Muhammad; Khan, Sardar; Khattak, Asif Khan; Khattak, Seema Anjum (Journal of Himalayan Earth Sciences, 2019)
This research work was intended to explore and analyze the quality of drinking water and associated health risk assessment at sources and consumption sites at Peshawar, Pakistan. For this purposes, the water samples were collected and analyzed for various parameters. The selected physicochemical parameters were pH, alkalinity, hardness, total suspended solids (TSS), electrical conductivity (EC), chlorides (Cl-), total dissolved solids (TDS), sodium (Na+), potassium (K+), nitrite (NO2-), magnesium (Mg2+) and calcium (Ca2+) while heavy metals included nickel (Ni), iron (Fe), copper (Cu), lead (Pb), manganese (Mn) and zinc (Zn). The physicochemical parameters were found within the limits set by World Health Organization's (WHO) except magnesium Mg2+ (246 mg/L) and Ca2+ (264 mg/L) at the end-user. In case of heavy metals, Pb (1.05 mg/L) concentration was higher in one sample at end-user point, while Ni (0.51 mg/L) was found above the allowable levels in all samples at water sources. The ADI (average daily intake) and HRI (health quotient) were calculated for heavy metals. HRI values were greater than 1 for Fe at source and for Fe, Cu, Zn, Ni, and Pb at end-user indicating that exposed populations could be at chronic risk. Comparison of source and end- user using unpaired t-test revealed that pH, TSS, Cl- and Cu levels of end-user were significantly higher (P<0.05). It is concluded that that the distribution network for the supply of drinking water is damaged and causing the contamination of the drinking water with heavy metals. Therefore, serious steps should be taken to avoid hazardous effects of toxic heavy metals.